2022
DOI: 10.1200/op.21.00875
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Related Medication Nonadherence and Patient Cost Responsibility for Rural and Urban Cancer Survivors

Abstract: PURPOSE: The relationship between out-of-pocket spending and cost-related medication nonadherence among older rural- and urban-dwelling cancer survivors is not well understood. METHODS: This retrospective cohort study used the Surveillance, Epidemiology, and End Results Program, Medicare claims, and the Consumer Assessment of Healthcare Providers and Systems survey linked data resource linked data (2007-2015) to investigate the relationship between cancer survivors' cost responsibility in the year before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…This is important as it refers to a condition for which patients must cover treatment cost out of their pocket, which has been shown to be a barrier to adherence. 30,31 As the majority of patients in our study were aged 55-75, our findings are in line with previous meta-analyses on the impact of pharmacists' interventions in older patients' adherence. Marcum et al concluded that irrespective of type, pharmacist-led interventions resulted in a significant improvement in adherence to medication in older adults.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is important as it refers to a condition for which patients must cover treatment cost out of their pocket, which has been shown to be a barrier to adherence. 30,31 As the majority of patients in our study were aged 55-75, our findings are in line with previous meta-analyses on the impact of pharmacists' interventions in older patients' adherence. Marcum et al concluded that irrespective of type, pharmacist-led interventions resulted in a significant improvement in adherence to medication in older adults.…”
Section: Discussionsupporting
confidence: 92%
“…This is important as it refers to a condition for which patients must cover treatment cost out of their pocket, which has been shown to be a barrier to adherence. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…This cross‐sectional study of a diverse sample of patients receiving support from PAF found cancer clinical trial‐related financial hardship, most often stemming from travel expenses, affects almost half of trial‐enrolled patients. Though financial hardship is a well‐documented adverse effect of standard‐of‐care cancer treatment, 25 , 26 , 27 , 28 , 29 this is one of the few studies to report on and quantify financial hardship and its impact on patients with lower incomes considering or participating in cancer clinical trials. Additionally, this study provides data on measures of both subjective financial hardship, or affordability, and objective financial hardship, or actual costs, as both are important in understanding potential financial barriers to clinical trial participation.…”
Section: Discussionmentioning
confidence: 99%
“…21 Thus, longitudinal financial hardship screening throughout treatment and into survivorship is needed to identify and mitigate financial hardship as patients incur more medical and nonmedical bills related to their cancer care. [22][23][24][25][26][27] Collection of patient economic data is also critical for tailored intervention development for health care systems in geographic areas where systemic issues, such as persistent poverty, Medicaid politics, and structural racism, create barriers to cancer care delivery. Notably, our sample is not nationally representative since 17% of Alabamians live below the federal poverty threshold compared with the national average of 13%.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is alarming since a recent study estimated 42% of individuals with cancer depleted their entire life assets within 2 years of their cancer diagnosis 21 . Thus, longitudinal financial hardship screening throughout treatment and into survivorship is needed to identify and mitigate financial hardship as patients incur more medical and nonmedical bills related to their cancer care 22–27 …”
Section: Discussionmentioning
confidence: 99%